Effect of using bentonite and vitamin C on some economic traits of local Arabian lambs - Noor Zwaid Haddad Al-Saa'di; Meitham K, Ali AL-Galiby (University of Thi-Qar Journal of agricultural research, 2021)
The current study was conducted in the animal field of the College of Agriculture and Marshlands / University of Thi-Qar for the period from 6/11/2020 to 16/2/2021 to know the effect of adding different percentages of bentonite and vitamin C to the diets of male Arabized lambs, as the study included the use of (16) males Arabized lambs, and the experiment lasted for 100 days. The lambs were taken after weaning at the age of 5 months, with an average weight of (28 kg ± 1.24). The animals were randomly divided into four groups, with four lambs per group. The first group-included animals fed the basic diet. T2 animals were fed with bentonite added to the basic diet at a rate of 20 g/kg dry weight, T3 were fed with vitamin C in the form of capsules at a rate of 50 mg/kg live weight in addition to the basic diet, while T4 animals treated with 10 g bentonite/kg dry weight added to the diet + 25 mg vitamin C / kg live weight provided to the animal in the form of capsules. Hay was offered freely to all the different transaction lambs. The results were statistically analyzed using the complete random design, a significant increase (P≤0.05) was observed in the average body weight, The average daily and total weight gain of the third group animals (treated with vitamin C) compared to the control group and the other treated groups, as the average body weight increased from the start of the eighth week until the twelfth week, a non-significant increase was also observed in the amount of feed consumed and the food conversion efficiency of the T3 group compared to the control group.